Analysis of Product Variation and Service Quality on Repurchase Intention Mediated by Customer Satisfaction - Afika Putri Anjani (Universitas Ciputra Surabaya, 2021)
The purpose of this study was to determine customer satisfaction as a mediating variable through product variations and service quality to repurchase intention. This research uses a quantitative method with 92 respondents of TB Triguna customers, this research uses a simple random sampling technique. Data collection techniques are using a questionnaire and data analysis used is using SmartPLS (SEM). The analysis technique used is the path analysis test with the aim to find out how much influence customer satisfaction as a mediating variable through product variation and service quality variables on repurchase intention. The results showed that product variation and service quality significantly influenced repurchase intention mediated by customer satisfaction. With each p-value < 0.05 so that the five hypotheses are accepted and indicate that the variable repurchase intention and customer satisfaction can be explained by variable variations in product and overall service quality by 89.7% and the rest is influenced by other factors outside the research model this is 10.3%.